Deradikalisasi Pemahaman Al Quran: Pendampingan Masyarakat Rawan Terpengaruh Gerakan Islam Garis Keras - Lutfiyah, Lujeng; Tamam, Ahmad Badrut; Muniroh, Alimul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2016)
Violence and radicalism in the name of religion which leads to terrorism has emerged as a complicated issue in contemporary Indonesian Islam. The emergence and development of radicalism were actually caused by a lack of understanding of the Qur’an. The verse of the Qur’an has been interpreted textually and partially. This, by far, are happened in Paciran Lamongan in the recent years. Reconstruction of understanding verse of the Qur’an on vulnerable communities that is easily affected by movement of Islamic radicalism has been properly carried out, so that it can give a new atmosphere, and it can be the prevention to face the violence movement. Deradicalization of understanding to the Qur’an is a solution-based action to prevent violence and radicalism in the name of religion.